Moving politics: Emotion and ACT UP’s fight against AIDS - Gould, Deborah B. (University of Chicago Press, 2009)
In the late 1980s, after a decade spent engaged in more routine interest-group politics, thousands of lesbians and gay men responded to the AIDS crisis by defiantly and dramatically taking to the streets. But by the early 1990s, the organization they founded, ACT UP, was no more—even as the AIDS epidemic raged on. Weaving together interviews with activists, extensive research, and reflections on the author’s time as a member of the organization, Moving Politics is the first book to chronicle the rise and fall of ACT UP, highlighting a key factor in its trajectory: emotion. Surprisingly overlooked by many scholars of social movements, emotion, Gould argues, plays a fundamental role in political activism. From anger to hope, pride to shame, and solidarity to despair, feelings played a significant part in ACT UP’s provocative style of protest, which included raucous demonstrations, die-ins, and other kinds of street theater. Detailing the movement’s public triumphs and private setbacks, Moving Politics is the definitive account of ACT UP’s origin, development, and decline as well as a searching look at the role of emotion in contentious politics.
https://transreads.org/wp-content/uploads/2021/07/2021-07-15_60f0412da8a40_deborah-gould-moving-politics-emotion-and-act-ups-fight-against-aids.pdf
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amériques; discipline; identités LGBTQIA2+; militance; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions; états-unis

Les menaces au droit à l’avortement et à l’autonomie des femmes enceintes - Lemonde, Lucie (Les Cahiers de droit, 2009)
Après un bref survol de l’histoire récente de la criminalisation de l’avortement au Canada, l’auteure présente les divers projets de loi privés touchant d’une façon ou d’une autre le droit à l’avortement, principalement le projet no C-484 sur l’homicide foetal, pour en saisir les conséquences sur le droit canadien et sur l’autonomie des femmes pendant leur grossesse. Ces projets de loi se situent à l’intérieur d’une stratégie des opposants à l’avortement qui a essentiellement pour objet de faire reconnaître en droit canadien un droit à la vie et à la sécurité aux foetus et de remettre en question le libre choix des femmes en la matière. Suit une discussion sur l’instrumentalisation du droit pénal à des fins de contrôle social de questions d’ordre éthique. Le texte se termine par une réflexion concernant l’intérêt de l’État dans la protection des foetus. L’auteure soutient que toute intervention étatique doit se faire dans le respect des droits constitutionnels des femmes, soit leur droit à la vie, à la santé et à la liberté.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; avortement; canada; cours; discipline; droit; droits des femmes*; justice reproductive; justice sociale; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques